2017
DOI: 10.1002/14651858.cd012832
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic urethral lift for the treatment of lower urinary tract symptoms in men with benign prostatic hyperplasia

Abstract: , P. (2017). Prostatic urethral lift for the treatment of lower urinary tract symptoms in patients with benign prostatic hyperplasia (Protocol). Cochrane database of systematic reviews (Online), 1-17. [CD012832.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…While including nine surgical treatment approaches, 109 trials, and 13 376 study participants, this review did not include the latest additions to the treatment armamentarium that were the focus of our review. Three relevant Cochrane reviews have been published, each focusing on single treatment modalities, namely, for PUL [21] , Aquablation [22] , and Rezūm [23] . For PUL with follow-up up to 24 mo, the review found that PUL may be less effective in relieving urinary symptoms but results in similar QoL.…”
Section: Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…While including nine surgical treatment approaches, 109 trials, and 13 376 study participants, this review did not include the latest additions to the treatment armamentarium that were the focus of our review. Three relevant Cochrane reviews have been published, each focusing on single treatment modalities, namely, for PUL [21] , Aquablation [22] , and Rezūm [23] . For PUL with follow-up up to 24 mo, the review found that PUL may be less effective in relieving urinary symptoms but results in similar QoL.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…PUL may preserve ejaculation and have fewer unwanted effects on erections than TURP. The authors further stated that there was uncertainty or no evidence about serious unwanted side effects or the need for additional treatment after surgery [21] . For Aquablation and based on limited follow-up up to 12 mo, the authors found that the effect on urological symptoms and QoL was probably similar to that of TURP.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…Основываясь на анализе десяти статей с шестью независимыми когортами пациентов, можно сделать вывод о хорошей переносимости и малой инвазивности данного метода, а также благоприятных результатах до 12 месяцев наблюдения. Во всех исследованиях отмечается положительное влиянии на эректильную и эякуляторную функцию в сравнении с более инвазивными трансуретральными вмешательствами [43]…”
Section: сравнительная характеристика современных методов хирургического лечения доброкачественной гиперплазии предстательной железы (литunclassified
“…In today's era, with the availability of numerous minimally invasive procedures to treat BPH, the findings of this Cochrane Review will be highly relevant to policymakers, healthcare providers and patients alike. We expect this review to complement a suite of related Cochrane Reviews focused on the endourological management (Jung 2017a) and vascular management (Jung 2017b) of LUTS related to BPH.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…Direct comparisons, for example of Aquablation and the water vapour thermal therapy would be helpful to compare their comparative e ectiveness. Cochrane Reviews for other relevant procedures are ongoing (Kang 2019;Jung 2017a;Jung 2017b;Mamoulakis 2014).…”
Section: Overall Completeness and Applicability Of Evidencementioning
confidence: 99%